Examining the relationship between antisocial behaviour and team performances in youth sports - Chan, Nicholas Yen Hau (2018)
Purpose: The purpose of this study is to examine the relationship between antisocial behaviour on team performance in youth sports, the potential implication of its relationship (or lack thereof), and any other potential relationship between moral behaviour and team successes in youth sports. Methods: Data was collected from 200 participants (aged 13 to 19) of youth sports team through a questionnaire consisting of the Prosocial and Antisocial Behaviour in Sport Scale (PABSS), and their team record. Results: Bivariate analyses indicated a negative relationship between antisocial behaviour towards teammates (r = - 0.39, p < 0.01) and performance with medium effect size, and a negative relationship between Antisocial Behaviour towards opponents (r = - 0.32, p < 0.01) and performance with medium effect size. However, no relationship were found with prosocial behaviour towards teammates (r = - 0.01, p > 0.05) and performance, and between prosocial behaviour towards opponents (r = - 0.01, p > 0.05) and performance. Conclusion: Coaches should not associate team performance with antisocial behaviour, nor emphasize performance climates which promotes antisocial behaviour, but promote mastery orientation climates for better team performances.